Concrete Structures Under Projectile Impact - Fang, Qin; Wu, Hao (Springer Nature Singapore : Imprint: Springer, 2017)
In this book, the authors present their theoretical, experimental and numerical investigations into concrete structures subjected to projectile and aircraft impacts in recent years. Innovative approaches to analyze the rigid, mass abrasive and eroding projectile penetration and perforation are proposed. Damage and failure analyses of nuclear power plant containments impacted by large commercial aircrafts are numerically and experimentally analyzed. Ultra-high performance concrete materials and structures against the projectile impact are developed and their capacities of resisting projectile impact are evaluated. This book is written for the researchers, engineers and graduate students in the fields of protective structures and terminal ballistics.